Biosynthetic mesh in hernia repair: A systematic review and meta-analysis - Iyad S. Al-Bustami; Thomas Clements; Dalya Ferguson; Alamin Harmouch; Oscar A. Olavarria; Julie L. Holihan (International Journal of Abdominal Wall and Hernia Surgery)
INTRODUCTION: Biosynthetic mesh is the latest class of hernia mesh. It is a slowly absorbable synthetic mesh and promises to reduce hernia recurrence and other complications, such as mesh infection, erosion, adhesions, and chronic pain. This study aims to systematically review the literature on biosynthetic mesh in ventral hernia repair. MATERIALS AND METHODS: A search of MEDLINE, Cochrane, and Scopus databases was conducted to identify studies using biosynthetic mesh in ventral hernia repair. The Strengthening the Reporting of Observational Studies in Epidemiology checklist was utilized to assess study quality. The primary outcome assessed was hernia recurrence. Secondary outcomes included surgical site infection (SSI), surgical site occurrence (SSO), and reoperation. Heterogeneity was assessed using I2, and a random effects model was used for meta-analysis. RESULTS: Thirty-six studies were included, all of which were observational. Follow-up ranged from 1 to 98 months postoperative. Hernia recurrence was reported in 35 studies, yielding a pooled recurrence rate of 10% (95% CI, 8%–12%). SSI was reported in 30 studies, with a pooled recurrence rate of 8% (95% CI, 6%–11%). SSO was reported in 29 studies and ranged from 1% to 56%. Reoperation was reported in 26 studies, with a pooled reoperation rate of 9% (95% CI, 6%–11%). CONCLUSIONS: This review underscores the paucity of high-quality studies on biosynthetic mesh. While observational studies of hernia repair using biosynthetic mesh suggest it may be safe with acceptable outcomes, high-quality trials with long-term follow-up are necessary before widespread implementation of these mesh types.